War-related orthopedic injuries: a comprehensive analysis from Benghazi medical center 2013-2016 - Alhoiti, Ayman; Abushaala, Hassan; Elfadli, Mustafa (International Journal of Research in Orthopaedics, 2024)
Background: The majority of war-related injuries involve the extremities and typically necessitate surgical intervention. These injuries are notably severe due to the impact of high-velocity rockets, including gunshot wounds and blast injuries. However, epidemiology of the war-related injuries of the last decade Libyan conflict remains under investigated. The study aimed to illustrate the characteristics of the cases volume, mechanism of injury, and the emergency department management protocol. Methods: A retrospective observational study included all patients admitted to the orthopedic department with war-related injuries between December 2013 and December 2016. Relevant data collected included patient demographics, injury patterns, and treatment modalities. The data was organized and analyzed using SPSS statistical software. Results: The 563 patients with war-related orthopedic injuries were treated during the study period. The highest percentage of patients were seen in 2015 (45%) and 2014 (44.2%), with a peak in July/summer months. Most patients were male (86.3%) with a mean age of 30.5 years. The most common causes of injury were gunshot wounds (36.1%) and explosions (28.2%), primarily affecting the upper (35%) and lower (29.3%) extremities. The 75.7% of injuries resulted in fractures, with 16.2% having associated injuries like bowel, nerve, and amputation. The most common emergency interventions were damage control surgery, debridement, and fixation. Conclusions: This data provides valuable insights into the complex nature of war-related orthopedic injuries and the challenges healthcare teams face in conflict-affected regions. The findings underscore the critical need to strengthen the resilience and capacity of medical systems to effectively address the specific needs of war trauma.